2023
DOI: 10.3389/fcvm.2023.1211458
|View full text |Cite
|
Sign up to set email alerts
|

The causal effects of genetically determined human blood metabolites on the risk of atrial fibrillation

Abstract: BackgroundBlood metabolites have been found related to atrial fibrillation (AF), but the causal role is still unclear. Mendel randomization (MR) can give information about the causality between blood metabolites and AF.MethodsTwo-sample MR analysis was used to evaluate the causality between 486 blood metabolites and AF. Firstly, the genome-wide association study (GWAS) data for AF (from Nielsen et al.) was analyzed and some metabolites were identified. Then another GWAS data for AF (from Roselli et al.) was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A recent MR investigation proposed similar conclusions with us. Their independent study extracted different IVs with a significant threshold at p < 1 × 10 -5 and came to similar results 44 .…”
Section: Discussionmentioning
confidence: 58%
“…A recent MR investigation proposed similar conclusions with us. Their independent study extracted different IVs with a significant threshold at p < 1 × 10 -5 and came to similar results 44 .…”
Section: Discussionmentioning
confidence: 58%
“…Uridine is involved in cellular signaling through P2Y receptors and can modulate systemic metabolism [47]. Recent data revealed that a higher level of plasma uridine reduces the tendency for atrial fibrillation and can be associated with a decreased atherosclerosis risk [48,49]. Our previous studies indicated that under ischemia and reperfusion conditions, uridine supplementation prevents myocardial redox dyshomeostasis and heart rhythm disorders [29,30].…”
Section: Discussionmentioning
confidence: 99%